Lack of infrastructural Maintenance Culture and its Effects on the Development of North-eastern Nigeria - Iliya, Umar; Maigari, Momsiri B.; Ishaku, Ndoya Tsun-Dudaya (Kashere Journal of Politics and International Relations, 2024)
Infrastructure have been one of the major sources of development of any country in the world, Nigeria inclusive and north eastern Nigeria in particular but lackadaisical attitude of north eastern zone on maintenance culture has negatively affected infrastructural development which is critical and essential to development of the zone. Poor maintenance culture has drawn north eastern Nigeria backward and one of the stride actions that could salvage the zone from the total mess of infrastructural decay is maintenance. From observation, the issue of the deployment in the zone is not completely the issue of infrastructures but the existing once are not been properly maintained This paper aimed at examining lack of maintenance culture through review of archival materials and participative observations. Poor leadership, corruption, attitudinal problem and lack of maintenance policy were identified as major causes of the menace. some of the objectives among others are: to inculcate the habit of maintenance cultures in the north eastern zone, to examine the extend at which relevant authorities help in project maintenance, to determine the importance of maintenance culture in the zone In conclusion, the paper recommends the inclusion of maintenance culture in national educational curriculum, maintenance policy formulation and appointment of facility managers among others as necessary steps towards making the zone to develop.